Pengaruh Pelatihan Bantuan Hidup Dasar Terhadap Motivasi Untuk Memberikan Pertolongan Pada Korban Henti Jantung Oleh Mahasiswa Pramugari - Niken Setyaningrum; Agung Rejecky (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
Background of Study : The first tretament or victims of cardiac arrest is strongly influenced by the quality of emergency services, but other factors that can be supportive is the right way to help when outside the hospital. Cardiac events can occur anywhere and at any time including on the plane. When traveling by plane, the cabin crew in the aircraft are required to be able to do the first handler in the event of cardiac arrest. One of the cabin crew is a flight attendant who is tasked with maintaining security and serving the needs of passengers. Flight attendant students are prospective flight attendants who are prepared to have these skills, so that it can cause motivation for flight attendant students when entering the workforce. The purpose of this study was to determine the effect of basic life support training on the motivation to provide assistance to victims of cardiac arrest by Stewardess Students at STTKD Yogyakarta. Methods : This study Led Pre experimental Design. Sampling research using random sampling. The study was conducted at the STTKD Yogyakarta. The sample size in this study were 25 respondents. Analysis of the data used is the Wilcoxon Signed Rank Test. Results : There was a difference in motivation before and after basic life support training in cardiac arrest victims by STTKD Stewardess Students in Yogyakarta with a value (p = 0.008). Conclusion : Basic life support training can increase the motivation of stewardess students to help victims of cardiac arrest. Keywords : Basic Life Support, Cardiac Arrest, Motivation, Stewardess Students Korespondensi: Niken Setyaningrum, Stikes Surya Global Yogyakarta, Blado Potorono Banguntapan, Bantul, DIY, Indonesia, 085292917222, nikensetyaningrum7@gmail.com.